Možnosti sociální inkluze osob bez domova v kontextu platné legislativy a nástrojů sociální politiky - Mandys, Jan (Univerzita Pardubice, 2008)
Homelessness represents an extreme form of social exclusion. Homelessness is connected with unemployment, health problems, and social-pathological phenomena (e. g. addictions, delinquency, etc.). Social service law defines social services which are provided for these persons. The problem of homeless people is solved by means of structural funds, and at the level of ward politics as well. Important guide-post for social inclusion of homeless people is the analysis of their needs and lifestyle.
Keywords: social politics; social services; homelessness; needs; social inclusion